Dirty angels [videorecording (DVD)] - Green, Eva, 1980-; Bakalova, Maria, 1996-; Rose, Ruby, 1986-; Gibbs, Jojo T. (Lionsgate, 2026)
When a group of schoolgirls is taken hostage in Afghanistan, an American soldier named Jake joins an all-women commando unit to liberate them.